Elevated Temperature Lithium-Ion Batteries Containing SnO2 Electrodes and LiTFSI-Pip14TFSI Ionic Liquid Electrolyte. Issue 4 (4th February 2017) - Böhme, Solveig; Kerner, Manfred; Scheers, Johan; Johansson, Patrik; Edström, Kristina; Nyholm, Leif
Abstract : The performance of lithium-ion batteries (LIBs) comprising SnO2 electrodes and an ionic liquid (IL) based electrolyte, i.e., 0.5 M LiTFSI in Pip14 TFSI, has been studied at room temperature (i.e., 22°C) and 80°C. While the high viscosity and low conductivity of the electrolyte resulted in high overpotentials and low capacities at room temperature, the SnO2 performance at 80°C was found to be analogous to that seen at room temperature using a standard LP40 electrolyte (i.e., 1 M LiPF6 dissolved in 1:1 ethylene carbonate and diethyl carbonate). Significant reduction of the IL was, however, found at 80°C, which resulted in low coulombic efficiencies during the first 20 cycles, most likely due to a growing SEI layer and the formation of soluble IL reduction products. X-ray photoelectron spectroscopy studies of the cycled SnO2 electrodes indicated the presence of an at least 10 nm thick solid electrolyte interphase (SEI) layer composed of inorganic components such as lithium fluoride, sulfates, and nitrides as well as organic species containing C-H, C-F and C-N bonds.